(untitled) (Baghdad Science Journal, 2011)
Sewage sludge samples were collected from Al-rasafa and Al-karkh refinement stations which represent the main stations of Baghdad city. Samples were collected from all treatment stages: before, after, and during refinement processes. The High Purity Germanium Coaxial Detector system with energy resolution 1.8 keV for energy line 1333 keV of Co – 60 radioactive sources was used to measure radioactivity from both natural and artificial sources. GENIE – 2000 analysis the results statistically and qualitatively. The results showed that all sewage sludge samples exhibited natural radioactive level and sometimes less than the international regular standards, but Al–Karkh station showed increment in radioactive levels than Al– Rasafa station. Cs – 137 artificial radionuclide was detected in the samples with low concentration.